Monomia lucida sp. nov., a new swimming crab (Crustacea: Decapoda: Portunidae) from the South China Sea - Koch, Milan; ĎuriŠ, ZdenĚk (Zootaxa, 2018)
A new species of the portunid genus, Monomia Gistel, 1848, is described from the South China Sea in Vietnam. Monomia lucida sp. nov. is morphologically most similar to M. argentata (A. Milne-Edwards, 1861), which was originally described from Sarawak, on the island of Borneo. In addition to the stout, forward-directed anterolateral teeth of the carapace, the subrectangular sixth segment of the male pleon, and the long and slender laterally bent first gonopods, adults of the new species reach a greater size, and can also be distinguished from M. argentata by the colour pattern on the natatory dactylus. The independent specific status of M. lucida sp. nov. is also supported by molecular evidence. Aside from a comparison of this new species with other known congeners, new photographs of the holotype of M. samoensis (Ward, 1939) are also provided.
Keywords: Animals; Brachyura; China; plavání; anatomické struktury zvířat; Animal Structures; krabi; zvířata; mužské pohlaví; Male; Decapoda (Crustacea); Decapoda; Malaysia; Swimming; Borneo; Malajsie; Vietnam; Čína